Color Terms in Moken Language - แก้วจันทร์เกตุ, วุฒินันท์ (Journal of the Faculty of Arts, Silpakorn University, 2019)
This article examines the color terms used by Mokens in Surin Island, Phangnga Province. The data were collected from the interview of 7 Moken in formants. It was found that there were five basic color terms : potiak 'white' kɛːtam 'black' mɛːlaːk 'red' kuɲit 'yellow', and ɲomoːɲ 'grue or green and blue'. The evolution of basic color terms, deased on in the Moken language are at the fourth stage. The non-basic color terms were leased two strategies of compounding words from basic color terms with modifies, and referring to natural objects.